A review of mechanism and adsorption capacities of biochar-based engineered composites for removing aquatic pollutants from contaminated water - Murtaza, Ghulam; Ahmed, Zeeshan; Dai, Dong-Qin; Iqbal, Rashid; Bawazeer, Sami; Usman, Muhammad; Rizwan, Muhammad; Iqbal, Javed; Akram, Muhammad Irfan; Althubiani, Abdullah Safar; Tariq, Akash; Ali, Iftikhar (Frontiers in Environmental Science, 2022)
Contamination of water by aquatic pollutants (antibiotics, heavy metals, nutrients and organic pollutants) has become the most serious issue of the recent times due to associated human health risks. Biochar (BC) has been deemed as an effective and most promising green material for the remediation of wide range of environmental pollutants. Due to its limited properties (small pore size and low surface functionality), pristine biochar has encountered bottlenecks in decontamination applications. These limitations can be rectified by modifying the pristine biochar into engineered biochar via multiple modification methods (physical, chemical and mechanical) thus improving its decontamination functionalities. Recently these engineered BCs /BC-based composites or BC composites have gathered pronounced attention for water decontamination due to fewer chemical requirement, high energy efficiency and pollutant removal capacity. Biochar-based composites are synthesized by mixing of biochar with various modifiers including carbonaceous material, clay-minerals, metals and metal oxides. They considerably modify the physiochemical attributes of biochar and increase its adsorption ability against various types of aquatic pollutants. Biochar-based composites proved efficient in eliminating target pollutants. The efficiency and type of a specific mechanism depends on various factors, mainly on the physicochemical characteristics and composition of the biochar-based composites and the target pollutants. Among the different engineered biochars, the efficiency of clay-biochar composites in removing the antibiotics, dyes, metals and nutrients was good. Findings of this review could help to develop a comprehensive understanding of using engineered biochars as effective materials for the remediation of contaminated water. Finally, gaps and challenges in research are identified, and future research needs are proposed.